Global, regional, and national burden of fracture of sternum and/or fracture of one or more ribs: a systematic analysis of incidence, YLDs with projections to 2030 - Wang, Zhizhi; Cai, Yikuan; Tong, Yu; Li, Huajie; Zhou, Hu; Ou, Tongyin; Ye, Tianlan; Zhang, Jiangsheng; Cai, Kaican; Chen, Zhiming (Frontiers in Public Health, 2025)
BackgroundSternal and/or rib fractures represent a growing global health challenge. Despite their significant clinical and public health implications, epidemiological studies on these injuries remain limited. Utilizing the Global Burden of Disease 2019 (GBD2019) database, this study evaluates the worldwide burden of sternal and/or rib fractures and projects trends through 2030 to inform policy development.MethodsWe analyzed global incidence, age-standardized incidence rate (ASIR), years lived with disability (YLDs), age-standardized YLD rate (ASYR) and estimated annual percentage change (EAPC) of sternal and/or rib fractures across geographic regions, nations, age-sex groups, and socio-demographic index (SDI) quintiles using GBD2019 data. The Bayesian age-period-cohort (BAPC) model was employed to forecast trends until 2030.ResultsIn 2019, global incident cases of sternal/rib fractures reached 4.1 million (44% increase since 1990), with YLDs at 190,000 (62% rise since 1990). While ASIR and ASYR showed modest declines, the absolute burden remained substantial. East Asia and high-income North America both exhibited the highest incident cases and YLDs. Central Latin America and Western Saharan Africa demonstrated the steepest incidence growth, whereas the Caribbean experienced the most pronounced YLD increases. Nationally, China reported the highest absolute burden, while Greenland had the highest ASIR and ASYR. Males carried over 60% of the burden. Also, there was a negative correlation between EAPC and national SDI. Projections indicate that the global burden of disease will continue to rise by 2030.ConclusionThe escalating burden of sternal/rib fractures demands targeted interventions. Prioritizing injury prevention in high-burden regions (e.g., East Asia), addressing male-dominated occupational/behavioral risks, and optimizing infrastructure such as medical transport in low-SDI settings are critical policy priorities. Sustained surveillance through standardized reporting systems is essential for monitoring progress.